Hardware-in-the-loop testing of control of a precooled desiccant air-cooling system - Haggag, Osama; Demir, Mehmet Hakan; Cetin, Sabri; Worek, William; Premer, Jeffrey; Pandelidis, Demis (Frontiers in Mechanical Engineering, 2023)
Increasing the energy efficiency of cooling of buildings is an important component of the management of global energy consumption. A super-efficient cooling system based on evaporation concept has been developed and initial simulation results using MATLAB/Simulink software tool have already been published by our team. In this paper, we present the results of hardware-in-the-loop (HIL) testing of the real time controller for the cooler. HIL testing is an engineering process where the actual controller hardware and software is implemented and interfaced to a real-time simulated model of the controlled system. Using HIL testing, many real-world problems can be fixed before testing on the actual prototype. Controller design is implemented on a small footprint industrial PC with CODESYS RTE and application code where the control software is implemented using IEC 61131-3 programming languages. Similarly, real-time thermodynamic and input-output variable-based model of the room, environment, cooler and its mechanical components (sensors, actuators) are modeled using another industrial PC with same software tools. HIL test results show very good agreement with the offline simulations.